PERBANKAN DALAM ERA BARU DIGITAL - Kholis, Nur (Economicus, 2018)
The development of technology today was being increased rapidly to facilitate all human activities in all fields, one of them was the financial activity. During this time, the answer to the financial activity was a banking services that practice conventionally. However, with the development, emerged a new platform called Financing Technology (FinTech) which began to replace some of the bank's position in the community. Then how the future fate of banks that practice conventionally in the midst of technological developments?